Clinical impact of pharmacokinetic interactions between the HCV protease inhibitor simeprevir and frequently used concomitant medications. (21st February 2018) - Marra, Fiona; Höner zu Siederdissen, Christoph; Khoo, Saye; Back, David; Schlag, Michael; Ouwerkerk‐Mahadevan, Sivi; Bicer, Ceyhun; Lonjon‐Domanec, Isabelle; Jessner, Wolfgang; Beumont‐Mauviel, Maria; Kalmeijer, Ronald; Cornberg, Markus
Abstract : Aims: Direct‐acting antiviral agents (DAAs) for the treatment of hepatitis C (HCV) can be associated with drug–drug interactions (DDIs) with concomitant medications. The practical clinical implications of such DDIs are poorly understood. We assessed the clinical impact of possible pharmacokinetic (PK) interactions between simeprevir and frequently prescribed concomitant medications. Methods: This post hoc analysis pooled data from nine studies which evaluated simeprevir (SMV)‐based interferon‐free HCV treatment. Three classes of frequently used concomitant medications of interest (CMOIs) were analysed [antihypertensive drugs (AHDs), anxiolytic drugs (AXDs) and lipid‐lowering drugs (LLDs)] and categorized as amber or green according to their DDI potential with SMV (green: no DDIs; amber: potential/known PK interactions). Concomitant medications not recommended to be coadministered with SMV were not included. The composite primary endpoint was defined as the frequency of either discontinuation, interruption or dose modification of the CMOI during 12 weeks of SMV treatment. Results: Few patients met the composite endpoint in the various subgroups. Patients on amber CMOIs tended to experience CMOI modification more often (13.4–19.4%) than those on green CMOIs (3.1–10.8%). There was no difference in the frequency of adverse events between patients taking green and those taking amber CMOIs. Conclusions: In this large pooled analysis, coadministration of the evaluated commonly prescribed medications with known or potential PK interactions with SMV was manageable and resulted in few adjustments of concomitant medications. Our method could serve as a blueprint for the evaluation of the impact of DDIs.